2019
DOI: 10.1016/j.scitotenv.2018.11.462
|View full text |Cite
|
Sign up to set email alerts
|

Modeling multi-decadal mangrove leaf area index in response to drought along the semi-arid southern coasts of Iran

Abstract: Leaf Area Index (LAI; as an indicator of the health) of the mangrove ecosystems on the northern coasts of the Persian Gulf and the Gulf of Oman was measured in the field and modeled in response to observed (1986-2017) and predicted (2018-2100) drought occurrences (quantified 22 using the Standardized Precipitation Index [SPI]). The relationship of LAI with the normalized difference vegetation index (NDVI) obtained from satellite images was quantified, the LAI between 1986 and 2017 retrospectively estimated, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 64 publications
(91 reference statements)
0
26
0
Order By: Relevance
“…The main step was the development of the models that was conducted in several phases. We first randomly divided the well data (72 locations) into two sets such that one set with 70% of locations (~50) was used for training the models and the remaining locations (~30% = 22 locations) were used for the validation [34,74,[88][89][90]. Regarding the set of influencing factors, we used correlation-based feature selection method [91] to measure the average merit of each factor for mapping the groundwater potential.…”
Section: Modeling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The main step was the development of the models that was conducted in several phases. We first randomly divided the well data (72 locations) into two sets such that one set with 70% of locations (~50) was used for training the models and the remaining locations (~30% = 22 locations) were used for the validation [34,74,[88][89][90]. Regarding the set of influencing factors, we used correlation-based feature selection method [91] to measure the average merit of each factor for mapping the groundwater potential.…”
Section: Modeling Methodologymentioning
confidence: 99%
“…Opposite to rainfall, river density has a reverse relationship with groundwater potential [32] because when the drainage density is lower, the infiltration and recharge are greater [29]. Land use presents the influence of human activities on the landscape evolutions [33][34][35]. Soil type indicates the filtration rate and, therefore, is another important factor for groundwater potential [36,37].…”
Section: Data Usedmentioning
confidence: 99%
“…Increasing annual average temperature and decreasing annual precipitation have directly influenced the mangrove ecosystems in the study area. In the last century, the SPI value and annual rainfall have decreased and led to frequent droughts in Qeshm Island as reported in the study by Mafi-Gholami et al (2017) [36]. They investigated the relationship between drought events and mangrove in the study area and found that mangrove areas are significantly related to the reduction in the annual rainfall and occurrence of more drought events.…”
Section: Driving Forces Of Luccmentioning
confidence: 71%
“…Analysis of intensity of changes in the three periods indicated high level of change in dense-vegetation class, attributing to high dependence and direct relation of this class to extent of precipitation and rainfall instability in the arid and ultra-arid climates. This has been especially evident from several droughts in the region as shown in the study by Mafi-Gholami (2017), who showed that the SPI index has been significantly less compared to previous years [36]. Also, the mangrove class showed significant changes compared to other classes.…”
Section: Patterns To Processes In Luccmentioning
confidence: 87%
See 1 more Smart Citation